Cytoadherence Properties of Plasmodium knowlesi-Infected Erythrocytes - Lee, Wenn-Chyau; Shahari, Shahhaziq; Nguee, Samantha Yee Teng; Lau, Yee-Ling; Rénia, Laurent (Frontiers in Microbiology, 2022)
Plasmodium knowlesi is responsible for zoonotic malaria infections that are potentially fatal. While the severe pathology of falciparum malaria is associated with cytoadherence phenomena by P. falciparum-infected erythrocytes (IRBC), information regarding cytoadherence properties of P. knowlesi-IRBC remained scarce. Here, we characterized the cytoadherence properties of RBC infected with the laboratory-adapted P. knowlesi A1-H.1 strain. We found that late stage-IRBC formed rosettes in a human serum-dependent manner, and rosettes hampered IRBC phagocytosis. IRBC did not adhere much to unexposed (unstimulated) human endothelial cell lines derived from brain (hCMEC/D3), lungs (HPMEC), and kidney (HRGEC). However, after being “primed” with P. knowlesi culture supernatant, the IRBC-endothelial cytoadherence rate increased in HPMEC and HRGEC, but not in hCMEC/D3 cells. Both endothelial cytoadherence and rosetting phenomena were abrogated by treatment of P. knowlesi-IRBC with trypsin. We also found that different receptors were involved in IRBC cytoadherence to different types of endothelial cells. Although some of the host receptors were shared by both P. falciparum- and P. knowlesi-IRBC, the availability of glycoconjugates on the receptors might influence the capacity of P. knowlesi-IRBC to cytoadhere to these receptors.